Central Control of Brown Adipose Tissue Thermogenesis - Morrison, Shaun F.; Madden, Christopher J.; Tupone, Domenico (Frontiers in Endocrinology, 2012)
Thermogenesis, the production of heat energy, is an essential component of the homeostatic repertoire to maintain body temperature during the challenge of low environmental temperature and plays a key role in elevating body temperature during the febrile response to infection. Mitochondrial oxidation in brown adipose tissue (BAT) is a significant source of neurally-regulated metabolic heat production in many species from mouse to man. BAT thermogenesis is regulated by neural networks in the central nervous system which responds to feedforward afferent signals from cutaneous and core body thermoreceptors and to feedback signals from brain thermosensitive neurons to activate BAT sympathetic nerve activity. This review summarizes the research leading to a model of the feedforward reflex pathway through which environmental cold stimulates BAT thermogenesis and includes the influence on this thermoregulatory network of the pyrogenic mediator, prostaglandin E2, to increase body temperature during fever. The cold thermal afferent circuit from cutaneous thermal receptors, through second-order thermosensory neurons in the dorsal horn of the spinal cord ascends to activate neurons in the lateral parabrachial nucleus which drive GABAergic interneurons in the preoptic area to inhibit warm-sensitive, inhibitory output neurons of the preoptic area. The resulting disinhibition of BAT thermogenesis-promoting neurons in the dorsomedial hypothalamus activates BAT sympathetic premotor neurons in the rostral ventromedial medulla, including the rostral raphe pallidus, which provide excitatory, and possibly disinhibitory, inputs to spinal sympathetic circuits to drive BAT thermogenesis. Other recently recognized central sites influencing BAT thermogenesis and energy expenditure are also described.